(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The application of the vocational and professional orientation test, Search Directed Self (SDS), to future high school graduates of public schools in the department of Quindío, is a face-to-face activity within the Student Permanence Support Program developed at the University of Quindío. It consists of workshops with small groups of students, guided by a facilitator and seeks that each student identifies the professions that respond to their skills and preferences, found by themselves, through a self-assessment on the activities they like to do, their skills, their abilities and the careers that attract their attention. At the end of the workshop the individual results are kept by each student and the idea is that they are used as the main input for a discussion in the family environment about the profession or trade that the student may choose and with the group results the profiles and aspirations of all students in the department, in each of the municipalities and of each educational institution are identified. There is a significant number of people aspiring to careers in Health, Engineering, Languages and Veterinary Medicine, compared to a smaller number with the required skills; many students show an aptitude for Arts and Social Work, but only a third aspire to related careers; in areas of Administration, Law, Design, Education, Nursing, Gastronomy and Psychology there is a good number of applicants and it is balanced with aptitudes and preferences.